SEKOLAH ISLAM TERPADU DALAM PETA SISTEM PENDIDIKAN NASIONAL - Suyatno Suyatno (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2015)
Integrated Islam schools emerged as a response to dissatisfaction Islamic movement activists against the national education system in Indonesia. National education system considered in the management of education perpetuates the dualism between religion and public education. Therefore, it takes a model of alternative educational institution capable of removing any educational practice dichotomous. During its development, paradox regarding the development of integrated Islamic school when they actually have to be part of the national education system. This study aims to answer the question of how the position of integrated Islamic schools in the National Education map? This study is a qualitative case study model. Data collection methods were participant observation, in-depth interviews, and documentation. Data was analyzed using inductive-qualitative analysis. The results showed that the integrated Islamic school is an integral part of the national education system. The indications are; the adoption of the curriculum of the ministry of education and culture, use of the name of the